Citizen-centric Governance Indicators : Measuring and Monitoring Governance by Listening to the People and Not the Interest Groups - Ivanyna, Maksym; Shah, Anwar (2012)
Governance indicators are now widely used as tools for conducting development dialogue, allocating external assistance, and influencing foreign direct investment. This paper argues that available governance indicators are not suitable for these purposes as they do not conceptualize governance and fail to capture how citizens perceive the governance environment and outcomes in their countries. The paper attempts to fill this void by conceptualizing governance and implementing a uniform and consistent framework for measuring governance quality across countries and over time based on citizens' evaluations. Using data from the World Values Survey (and other sources) we implement this framework into practice and build citizen-centric governance indicators for 120 countries over the period 1994 to 2005.